AGE Related Histomorphological Study of Splenic Parenchyma in Goat (Capra hircus) - Waghaye, Jitendra; Banubakode, Sanjay; Charjan, Rupali; Rana, Jigyasa; Nandeshwar, Naresh (Indian Journal of Veterinary Anatomy, 2018)
The present study was conducted on goat spleen from prenatal to four months and above age. The small pieces from spleen were processed for histomorphological study. The general histoarchitecture of parenchyma of spleen showed that the cellular and fibrous reticulum was present throughout the splenic pulp in all age groups. White and red pulp was the two major components of splenic parenchyma. During early to mid prenatal age in group I, tissues of white pulp were in the form of diffused lymphoid patches of lymphocytes scattered throughout the red pulp. The formation of white pulp was completed without any patches of lymphocytes in red pulp towards the late prenatal stage. The white pulp nodules were round to ovoid in shape in all groups. These nodules showed highly significant increase in size with the advanced age. In all groups, the tissue of white pulp was delimited from surrounding red pulp by a marginal zone. The red pulp consisted of lymphocytes, reticular cells, erythrocytes, granulocytes, macrophages and few mast cells in all age groups. In addition, the megakaryocytes were found scattered throughout the red pulp in group I but were absent in group II, III, and IV. Fairly more number of plasma cells and macrophages were noted in group III and IV, which indicates increased phagocytic activity and maximum immunity level of organ. The sinuses of red pulp was poorly developed in early to mid prenatal age, but were found well developed and anatomised in other three groups.